(untitled) (KYAMC Journal, 2013)
Skin is the organ which covers our whole body and its condition directly influences our well being. Its psychological impacts are enormous, as evident by the efforts we put for taking care of our skin condition. The aim of this study was to find the presence of depression among the patients with dermatological disorders. Total 100 dermatological patients were assessed by the Hamilton Depression Rating Scale (HAM-D), 38% of patients had depression. Depression was highest in atopic dermatitis (71.43%), followed by psoriasis (58.82%), acne vulgaris (47.62%) and vitiligo (44.44%). Suicidal ideation was more common patient with atopic dermatitis (28.57%, 2 among 7) followed by psoriasis (23.53%, 4 among 17). DOI: http://dx.doi.org/10.3329/kyamcj.v2i2.13260 KYAMC Journal Vol.2(2) January 2012, 164-171